(untitled) (Ameghiniana, 2014)
The ammonite genera Hysteraceras Hyatt and Dipoloceras Hyatt are described from Patagonia for the first time. Three species are recognized from the Río Mayer Formation in Estancia La Vega, including Hysteraceras leanzai sp. nov., Dipoloceras elegans Haas and Dipa/aceras cristaium (Brongniart). Comparison with species from the Albian of Europe, Africa and Madagascar confirmed the early Late Albian age of the part of the Río Mayer Formation in which they occur.